Inspeção de peças com MPS Festo utilizando robô industrial e visão computacional: estudo de caso de classificação de peças. - Santos, Alerrandro Souza dos (Brasil, 2024)
In view of the importance of optimizing production processes and guaranteeing quality in industry, research is being carried out into parts inspection using Festo's modular production system (MPS), industrial robots and computer vision, in order to develop an efficient parts sorting system. To do this, it is necessary to explore the concepts of industrial automation and industrial robots, detail the methodology for implementing the system and analyze the results obtained. An applied study is then carried out, verifying that the proposed system improves accuracy, reduces inspection time and reduces incorrect disposal, which leads to the conclusion that the integration of robotics and computer vision is effective for automated inspection.